The Influence Of Social Networks On The Success Of Umkm Entrepreneurs: A Study On Indonesian Entrepreneurs - Suldina, Farida (International Journal Labs, 2023)
In the digital era and the development of information technology, social networks have become an important platform for communication and interaction between individuals and businesses. In Indonesia, Micro, Small and Medium Enterprises (MSMEs) play a vital role in the country's economy. The purpose of this study is to analyze the extent to which the use of social networks affects entrepreneurial success in MSMEs in Indonesia. This study used quantitative research methods. Data is collected through a survey involving entrepreneurs from various MSMEs in Indonesia. The data collected will be analyzed using regression analysis. The results showed that social networking has a positive influence on entrepreneurial success in MSMEs. Social networking can help MSMEs to expand business networks, obtain market information, and increase sales. MSMEs that want to increase their business success can utilize social networking as one of their strategies.